Transmission and clinical characteristics of coronavirus disease 2019 in 104 outside‐Wuhan patients, China. Issue 10 (11th July 2020) - Qiu, Chengfeng; Deng, Ziwei; Xiao, Qian; Shu, Yuanlu; Deng, Ye; Wang, Hongqiang; Liao, Xin; Liu, Huiwen; Zhou, Dinghui; Zhao, Xiang; Zhou, Jianliang; Wang, Jin; et al.
Abstract: Cases of coronavirus disease 2019 (COVID‐19) emigrating from Wuhan escalated the risk of spreading the disease in other cities. This report focused on outside‐Wuhan patients to assess the transmission and clinical characteristics of this illness. Contact investigation was conducted on each patient who was admitted to the assigned hospitals in Hunan Province (geographically adjacent to Wuhan) from 22 January to 23 February 2020. Cases were confirmed by the polymerase chain reaction test. Demographic, clinical, and outcomes were collected and analyzed. Of the 104 patients, 48 (46.15%) were cases who immigrated from Wuhan; 93 (89.42%) had a definite contact history with infection. Family clusters were the major body of patients. Transmission along the chain of three "generations" was observed. Five asymptomatic infected cases were found and two of them infected their relatives. Mean age was 43 (range, 8‐84) years, and 49 (47.12%) were male. The median incubation period was 6 (range, 1‐32) days, which of 8 patients ranged from 18 to 32 days, 96 (92.31%) were discharged, and 1 (0.96%) died. The average hospital stay was 10 (range, 8‐14) days. Family but not community transmission became the main body of infections in the two centers, suggesting the timely control measures after the Wuhan shutdown worked well. Asymptomatic transmission demonstrated here warned us that it may lead to the widespread of COVID‐19. A 14‐day quarantine may need to be prolonged. Highlights: The smoothly increase in the cumulative number of confirmations of the two centers indicates that the timely control measures work well, family clusters represent as the major body of infections, transmission along the chain of 3 "generations" was observed. No gender difference of patients was found, indicating male and female may have the same susceptibility of this illness. But the asymptomatic transmission demonstrated here warned us it may bring more risk to the spread of COVID‐19. The differences in demographics and clinical characteristics between emigrated patients and indigenous cases were not significant.